Digital marketing: a study of brazilian scientific production between 1999 and 2016 (Research, Society and Development, 2020)
Bibliographic studies are used to understand publications from different areas and themes of scientific research. Regarding digital marketing, no study has been conducted. What's more, the internet, coupled with marketing, is key to bringing organizational results. In this sense, the present work aimed to analyze the publications on the theme digital marketing. Thus, a qualitative and quantitative research was conducted, analyzing articles from 1999 to 2016, collected through the SPELL platform. In all, 203 articles related to digital marketing were analyzed. The results pointed out the main characteristics of research on the subject, such as journals, most studied themes, most used methods, data collection and analysis, consumers and digital media researched. In addition, there is an increase in publications from 2014, thus noting the importance of generating more knowledge about digital marketing.